Trends in cutaneous squamous cell carcinoma on the lip incidence and mortality in the United States, 2000–2019 - Zhang, Jin; Yang, Quyang; Wu, Jinyan; Yuan, Ruoyue; Zhao, Xiansheng; Li, Yue; Cheng, Xiujun; Wu, Baojin; Zhu, Ningwen (Frontiers in Oncology, 2023)
Objective This study provided a systematic analysis of the trend in incidence and incidence-based mortality for cutaneous squamous cell carcinoma (cSCC) on the lips in the USA using demographic characteristics from the Surveillance, Epidemiology, and End Results (SEER) database. Methods Patients diagnosed with cSCC on the lips between 2000 and 2019 from the 17 registries of the USA were identified. Incidence and incidence-based mortality rates were analyzed using SEER*Stat 8.4.0.1 software. This paper calculated incidence rates and incidence-based mortality rates by 100,000 person-years for sex, age, race, SEER registries, median household income ($/year), rural-urban distribution, and primary site. The annual percent changes (APC) in incidence and incidence-based mortality rates were then calculated using joinpoint regression software. Results Among 8,625 patients diagnosed with cSCC on the lips from 2000 to 2019, men (74.67%), white (95.21%), and 60–79 years old were the most common population, and 3,869 deaths from cSCC on the lips occurred. The overall incidence of cSCC on the lips was 0.516 per 100,000 person-years. cSCC on the lip incidence rates were highest among men, white, and patients aged 60–79 years old. cSCC on the lip incidence rates decreased by 3.210%/year over the study period. The incidence of cSCC on the lips has been decreasing in all sexes, ages, high- or low-income households, and urban or rural patients. The overall incidence-based mortality rate of cSCC on the lips during 2000–2019 was 0.235 per 100,000 person-years. cSCC on the lip incidence-based mortality rates were highest among men, whites, and people older than 80 years old. cSCC on the lip incidence-based mortality increased by 4.975%/year over the study period. cSCC on the lip incidence-based mortality rates increased for all sexes, races, ages, primary sites, high- or low-income households, and urban or rural patients during the study period. Conclusion Among patients in the USA diagnosed with cSCC on the lips from 2000 to 2019, the overall incidence decreased by 3.210% annually, and incidence-based mortality increased by 4.975%/year. These findings update and supplement the epidemiological information of cSCC on the lips in the USA.